This is a result that seems pretty easy to prove, yet it is given as a corollary (3.12) in Atiyah Macdonald - I'm not sure if the previous result (that localisation commutes with taking radicals) is necessary to prove this, or if it is just given as a 'nice' application.

The statement is that

If $N$ is the nilradical of $A$ then $S^{-1}N$ is the nilradical of $S^{-1}A$.

If $x/s$ is some nilpotent in $S^{-1}A$, then $x^k/s^k = 0$ for some $k$, so that $x^k = 0$ and so $x \in N$, i.e. $x/s \in S^{-1}N$. Conversely if $x/s \in S^{-1}N$ then $x$ must be nilpotent in $A$, hence $x/s$ is nilpotent in $S^{-1}A$.

This proof seems incredibly straightforward so I'm not sure what I'm missing.

  • 1
    $\begingroup$ "so that $x^k=0$" is not quite true. Recall when a fraction equals zero in a ring of fractions. $\endgroup$ – user26857 Feb 2 at 8:18
  • $\begingroup$ Perfect, I knew I was missing something simple. If $x^k = 0$ in $S^{-1}A$ then $x^k t u = 0$, so we can't say $x \in N$. Thanks! $\endgroup$ – nhmwhhxx Feb 2 at 10:02
  • $\begingroup$ @nhmwhhxx: Yes, $x$ may not be in $N $, but $xtu$ is in $N$ and that's enough to conclude that $x/s=(xtu)/(stu)\in S^{-1}N $. $\endgroup$ – Shivering Soldier Feb 2 at 12:29

As per the comments, the line

$x^k/s^k = 0$ so that $x^k = 0$

is not correct. For $x^k/s^k =0 $ in $S^{-1}A$, all that this says is that there exist $t, u \in A$ so that $x^ktu = 0$ in $A$.

On the other hand, $xtu$ is in $N$, and so $x/s = (xtu)/(stu) \in S^{-1}N$, which is what we wanted.

| cite | improve this answer | |
  • $\begingroup$ If $a/b = 0$ in $S^{-1}A$ then $ta = 0$ for some $t \in S$. You just need one element, not two and that element is in $S$ not just in $A$. So we have $tx^k = 0$ which means $(tx)^k = 0$ which means $tx \in N$. $\endgroup$ – Trevor Gunn Mar 29 at 2:29

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.